Determinants and Gaps in Preventive Care Delivery for Indigenous Australians: A Cross-sectional Analysis - Bailie, Christopher; Matthews, Veronica; Bailie, Jodie; Burgess, Paul; Copley, Kerry; Kennedy, Catherine; Moore, Liz; Larkins, Sarah; Thompson, Sandra; Bailie, Ross Stewart (Frontiers in Public Health, 2016)
Background Potentially preventable chronic diseases are the greatest contributor to the health gap between Aboriginal and Torres Strait Islander peoples and non-Indigenous Australians. Preventive care is important for earlier detection and control of chronic disease, and a number of recent policy initiatives have aimed to enhance delivery of preventive care. We examined documented delivery of recommended preventive services for Indigenous peoples across Australia, and investigated the influence of health center and client level factors on adherence to best practice guidelines. Methods Clinical audit data from 2012-2014 for 3623 well adult clients (aged 15-54) of 101 health centers from four Australian states and territories were analyzed to determine adherence to delivery of 26 recommended preventive services classified into five different modes of care on the basis of the way in which they are delivered (eg. basic measurement; laboratory tests and imaging; assessment and brief interventions, eye, ear and oral checks; follow-up of abnormal findings). Summary statistics were used to describe the delivery of each service item across jurisdictions. Multilevel regression models were used to quantify the variation in service delivery attributable to health center and client level factors and to identify factors associated with higher quality care. Results Delivery of recommended preventive care varied widely between service items, with good delivery of most basic measurements but poor follow-up of abnormal findings. Health center characteristics were associated with most variation. Higher quality care was associated with Northern Territory location, urban services and smaller service population size. Client factors associated with higher quality care included age between 25-34 years, female sex and more regular attendance. Conclusions Wide variation in documented preventive care delivery, poor follow-up of abnormal findings, and system factors that influence quality of care should be addressed through CQI approaches that engage stakeholders at multiple levels (including, for example, access to care in the community, appropriate decision support for practitioners, and financial incentives and context appropriate guidelines).